2017
DOI: 10.4014/jmb.1605.05036
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Interphase Microbial Community in Luzhou-Flavored Liquor Manufacturing Pits of Various Ages by Polyphasic Detection Methods

Abstract: It is vital to understand the changing characteristics of interphase microbial communities and interspecies synergism during the fermentation of Chinese liquors. In this study, microbial communities in the three indispensable phases (pit mud, zaopei, and huangshui) of Luzhou-flavored liquor manufacturing pits and their shifts during cellars use were first investigated by polyphasic culture-independent approaches. The archaeal and eubacterial communities in the three phases were quantitatively assessed by combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 40 publications
(53 reference statements)
1
34
0
Order By: Relevance
“…Bacillus can also produce aromatic and phenolic compounds, which improve the sensory appeal of the liquor . Lactobacillius and Lactococcus are common bacteria in jiuqu , and produce lactic acid which contributes to the formation of ethyl lactate, which is a vital flavour compound in light flavour type liquor . When considering low abundance bacteria, Gluconobacter oxydans , Oceanbacillus profundus , Weissella paramesenteroides , Methylobacterium aquaticum , Bacillus oleronius and Bacillus ginsengihumi occurred at different times in the liquor brewing process and further investigation is required to understand their contribution to the liquor brewing process.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus can also produce aromatic and phenolic compounds, which improve the sensory appeal of the liquor . Lactobacillius and Lactococcus are common bacteria in jiuqu , and produce lactic acid which contributes to the formation of ethyl lactate, which is a vital flavour compound in light flavour type liquor . When considering low abundance bacteria, Gluconobacter oxydans , Oceanbacillus profundus , Weissella paramesenteroides , Methylobacterium aquaticum , Bacillus oleronius and Bacillus ginsengihumi occurred at different times in the liquor brewing process and further investigation is required to understand their contribution to the liquor brewing process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, C. ljungdahlii was able to cometabolize CO 2 and H 2 to acetate and ethanol, which can be used for the production of butyrate and caproic acid by C. kluyveri (Richter, Molitor, Diender, Sousa, & Angenent, ). Another synergistic interaction is the interspecies hydrogen transfer (Thauer, Kaster, Seedorf, Buckel, & Hedderich, ), as the existence of many hydrogen producing Clostridium bacteria and methanogenic archaea in the SFB ecosystem (Ding et al., , , ; Hu et al., ; Li et al., ; Luo et al., ; Tao et al., ; Wu, Ding, Huang, & Zhou, ; Zheng et al., ). Interspecies hydrogen transfer between Clostridium and methanogenic archaea is beneficial to maintain the stability of the community and niches and also for the forming of many valuable metabolites (Hu et al., ).…”
Section: Interspecies Interactionsmentioning
confidence: 99%
“…Other studies revealed that C. kluyveri was in highly co‐occurrence with the Methanobacteria class (Hu et al., ) . Methanobacterium is one of the predominant genera found in different pit muds (Ding et al., , , ; Hu et al., ; Li et al., ; Luo et al., ; Tao et al., ; Wu et al., ; Zheng et al., ) and Zaopei (Li et al., ; Sun et al., ). In addition, C. tyrobutyricum isolated from pit mud did not produce caproic acid in monoculture, but the yield of caproic acid reached 1.8 g/L when it was cocultured with Bacillus (unpublished data).…”
Section: Interspecies Interactionsmentioning
confidence: 99%
“…These samples were pretreated prior to examination according to the method described by Li et al [22].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…It has been used to characterize the archaeal community in complex environments [18,19]. In our previous researches, the microbial communities in PM were characterized by FISH using various order-specific oligonucleotide probes [20][21][22][23][24]. The composition of four orders methanogenicarchaeal (methanosarcinales, methanobacteriales, methanomicrobiales and methanococcales) in various aged PM were also estimated quantitatively [25].…”
Section: Introductionmentioning
confidence: 99%